Пріоритетні галузі виробництва підприємців Волині (друга половина XIX – початок ХХ ст.) - Романюк, Неля Йосипівна; Romaniuk, N.J. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Досліджено показники обсягів виробництва в сільському господарстві та промисловості Волинської губернії періоду реформувань 1861–1914 рр, запровадження підприємцями найбільш вигідних в умовах краю галузей виробництва. Article investigates production volume indicators of agricultural and industrial production in Volyn governorate when under the influence of reforms of 60–70 s of the XIXth century and Stolypin’s agrarian policy appeared market relations, business has been developing and production was intensified. We have analyzed implementation of the most favourable for this zone production branches by local businessmen. Leadership in growing production capacities took agricultural entrepreneurs – landowners, prosperous countrymen, who were able to use land ownership to their benefits and receive profit in production of agricultural products and industry. Prominent proprietors such as the Tereshchenko, the Pototskyi, the Sangushko, the Radzyvill and many others managed to find the most profitable types of business activities – crops, sugar beet, potato, hop growing, establishment of personal sugar, grain, malt distillery enterprises, beer factories, other enterprises and mills. Significant production capacities were achieved by the entrepreneurs in wood-processing, glass, china, paper, cement branches of production.
Priority Industries of Manufacturers in Volyn (the Second Half of XIXth – beg. of XXth Century)
Романюк Н. Пріоритетні галузі виробництва підприємців Волині (друга половина XIX – початок ХХ ст.)// Науковий вісник Східноєвропейського національного університету ім. Лесі Українки. Серія: історичні науки. Луцьк 2015. Вип. 5 (306). - С.21-27.
Keywords: entrepreneurship; landowners; agriculture; підприємництво; землевласники; сільське господарство